Decision-making in the woman-midwife dyad : a relational undertaking : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Midwifery at Massey University, Manawatu, New Zealand - Noseworthy, Dorothy Ann (Massey University, 2013)
Within midwifery in both Canada and New Zealand informed choice and decisionmaking is a strong tenet of the profession’s philosophy and ethics. Through discussions and conversations, decision-making was explored in the womanmidwife dyad with birth of the placenta as the vehicle. Using various epistemological, theoretical principles and philosophical paradigms, as well as acknowledging the research journey itself, this thesis develops not only a model that increases the understanding of decision-making but a new relational research methodology that is fitting for midwifery and other health disciplines in which longterm relationships are established. The evolving methodology developed from the challenges of the research journey and the steps undertaken to address the challenges. These steps involved consultation, professional networks, building relationships and adapting to circumstances. Participants were recruited through professional networks and involved 14 woman-midwife relationships. In total 14 women, 5 support persons, and 18 midwives were involved from New Zealand and Ontario, Canada. The stories, experiences, and thoughts of each woman, her support person, and the midwives in the childbearing relationship were gathered through recording of the decision-making discussions and conversational interviews. The resulting methodology, which is presented in the first substantive chapter, recognises the complexity of influences on the researcher and participants and their involvement together, in constructing knowledge. Influenced by Granovettor’s (1985) concepts of embeddedness and Sherwin’s (1998) broader definition of relationality, the findings identify how identity projects, philosophies, socio-political, and locational events influence decision-making within the woman/family-midwife partnership. Participant’s talk as a whole and in part were analysed using social theories of identity, including narrative identity, positioning, location, professional projects, and power. The central finding in this research is that decision-making in the woman/family-midwife partnership is relational in nature, influenced by social networks and the historical, social, political, and economic contexts and locations in which they are embedded.
Keywords: Midwifery; Decision-making